"The Place That Holds Our Stories": The National AIDS Memorial Grove and Flexible Collective Memory Work. (30th November 2017) - Gamson, Joshua
Abstract: Through a qualitative, extended case study of the National AIDS Memorial Grove (NAMG) in San Francisco's Golden Gate Park, the only federally designated AIDS memorial in the United States, this article investigates collective memory as an organizationally bounded process. After locating the case in the scholarship on collective memory conflicts, and on complex and reflexive memorials, I suggest that the NAMG highlights the interaction between impulses within collective memory work that stand in tension. In the political struggle over the what, why, who, and how of memorializing at the NAMG and elsewhere, we can see an encounter between the forces of resolution, fixity, and unitary voice and those of openness, reflexivity, and multivocality. In the case of the NAMG, the balance has interestingly tipped towards the latter, what I call flexible memory production : the NAMG operates with relatively broad, porous categories of "victims" and "survivors, " and deliberately pursues nonlinear, fluid, decentered storytelling. My discussion then points to the conditions that enable and encourage such flexibility—the characteristics of the trauma itself; organizational conditions; and the features of memory technologies—and those that push back against it, within and beyond the Grove case. I conclude with a consideration of whether and how unsettled, mutable, flexible memory projects can be sustained over time.